Uprawnienia Rzecznika Praw Obywatelskich w zakresie prawa do ochrony zdrowia na przykładzie wybranych wystąpień generalnych w latach 2011–2013 - Klepacki, Kamil (Wydawnictwo Naukowe UAM, 2014)
The Ombudsman’s activity in the scope of the right to health protection refl ects the modern concept of a Spokesman being a constitutional organ for the protection of human and civil rights and freedoms. The deliberations in this paper focus on the right to health protection and, in particular, the Ombudsman’s performance with regards the assurance of its proper exercise. A special attention is put on Ombudsman’s general presentations. His other competences are also mentioned. General presentations are manifestations of the Ombudsman’s special activity, and concern systemic problems that frequently result from multiplied individual complains regarding an identical problem. Thus they may contain opinions as well as requests demanding a certain manner of solving a problem, or requests for instituting disciplinary proceedings, for taking a legislative initiative, or issuing or amending existing legal acts. There are close to 60 000 applications and requests addressed to the Ombudsman yearly. The diversity of problems and the fast changing legal system have enforced the author of this paper to focus on selected issues only. Hence the emphasis on the Ombudsman’s general presentations in 2011–2013. Annual information provided by the Ombudsman was analysed in detail. Further, the information delivered at parliamentary meetings (to the Sejm and the Senate) as well as the source materials and the answers to questions posed after general presentations are analysed. As can be seen, the problems under Ombudsman’s consideration in the health protection area included assistance provided to the elderly and medical services available to detainees and children in police children’s rooms.
Ombudsman’s competences in the scope of the right to health protection on the example of selected general presentations in 2011–2013
Keywords: rights to health protection; Ombudsman’s competences; general presentations; health protection system